2013
DOI: 10.1002/ejoc.201300834
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Hydrolysis of Aryldiazonium Ions Revisited: Marcus Theory vs. Canonical Variational Transition State Theory

Abstract: Several models, theoretical levels and computational methods, all based on the canonical variational transition state approximation, have been used to predict both the experimental activation energies (ΔEexp≠) and the experimental activation free energies (ΔGexp≠) for the hydrolysis of aryldiazonium ions. It is demonstrated that the computation of activation energies (ΔE≠), instead of activation free energies (ΔG≠), agrees better with the corresponding experimental data, showing that the employed computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…It is interesting to note that the pretreatment protocol results in the formation of −OH groups, and it is therefore likely that the functionalization mechanism involves nucleophilic attack of the hydroxyl onto the electron deficient para position of the aryl ring, in analogy to the S N 1 hydrolysis mechanism of aryldiazonium cations (see Scheme S1). As regards stainless steel functionalization, most previous reports make use of cathodic electrografting reactions that can be driven even in the presence of a continuous passive oxide. Small et al recently reported on the spontaneous attachment of fluorinated aryldiazonium salts on stainless steel from solution, achieved by polishing samples immediately prior to modification. Mechanical polishing breaks down the steel passive oxide, exposing the iron-rich underlayer which can act as an effective spontaneous reductant in aryldiazonium grafting, in agreement with findings on various oxide-free metals .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that the pretreatment protocol results in the formation of −OH groups, and it is therefore likely that the functionalization mechanism involves nucleophilic attack of the hydroxyl onto the electron deficient para position of the aryl ring, in analogy to the S N 1 hydrolysis mechanism of aryldiazonium cations (see Scheme S1). As regards stainless steel functionalization, most previous reports make use of cathodic electrografting reactions that can be driven even in the presence of a continuous passive oxide. Small et al recently reported on the spontaneous attachment of fluorinated aryldiazonium salts on stainless steel from solution, achieved by polishing samples immediately prior to modification. Mechanical polishing breaks down the steel passive oxide, exposing the iron-rich underlayer which can act as an effective spontaneous reductant in aryldiazonium grafting, in agreement with findings on various oxide-free metals .…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that, as in the case of reactions with primary alcohols, functionalization proceeds via nucleophilic substitution involving oxide hydroxyl groups (see Scheme S1). 56 Field Tests of Bare and Lactose-Modified Surfaces. Control and lactose-modified coupons remained immersed in Figure 6.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is, however, set against the indivisible quantum nature of the electron. Thus, in the case of diabatic inner-shell reactions, the SET process (electron jumping) occurs at the cross point of the R and P parabolas, which represents the transition state (TS) of the reaction. , Therefore, accordingly to the MT, the activation free energy (Δ G ≠ ) for SET reactions in polar solvents is a nonlinear function of the free energy of reaction (Δ G ) and the barrier height for Δ G = 0, called the intrinsic reaction barrier (Λ), as shown by eq . The Λ value is related to the most popular reorganization energy (λ) by the expression: Λ = λ/4. Others and we have used eq successfully for the computation of reaction barriers for the hydration of several carbocations. For adiabatic reactions, the TS are tunneled and the reaction profile is different (red line in Figure ). The adiabaticity of a reaction is measured by the overlapping (coupling) Hamiltonian ( H ) between the IS and FS at the TS (Figure ).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…A particularly popular choice of DFA in such studies is B3LYP. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Beyond DFT, common methods employed in computational studies of hydrolysis reactions include Hartree-Fock (HF) 23,25,31,35,45 and second order Møller-Plesset perturbation theory (MP2), [23][24][25]30,32,47,48 with less frequent use of higher-order Møller-Plesset perturbation theory, 24,30,49 coupledcluster, 25,47 and configuration-interaction methods. 30,31,48 While numerous benchmark studies have been conducted to evaluate the performance of various exchange-correlation density functional approximations (DFAs) for the prediction of reaction thermochemistry, [50][51][52][53][54][55][56][57]…”
Section: Introductionmentioning
confidence: 99%